Cysteamine ophthalmic solution 0.44% for the treatment of corneal cystine crystals in cystinosis. (August 2013) - Huynh, Nancy; Gahl, William A; Bishop, Rachel J
Cystinosis is a rare autosomal recessive disease caused by abnormal accumulation of the amino acid cystine within lysosomes of various cells throughout the body, leading to multiple organ damage. Corneal cystine crystals are an ocular manifestation of cystinosis. Untreated, these corneal deposits worsen with time, often resulting in photophobia, ocular discomfort, blurred vision, and in severe cases, recurrent epithelial erosions, and band keratopathy. Oral cysteamine stabilizes renal and other systemic functions in these patients, but has no effect on cystine crystal accumulation in the cornea, due to the absence of a direct blood supply to the cornea. Cysteamine ophthalmic solution 0.44% reduces corneal cystine crystal deposition, helps clear existing crystals and is currently the only US FDA-approved therapy for the treatment of the corneal crystal involvement of cystinosis.